An Assessment of Liquid Biofuel Value Chains from Heavy-Metal Contaminated Feedstock - Dimitrios Giannopoulos; Ilias Katsifis; Dimitrios Katsourinis; Athanasios Rentizelas; Maria Founti (Fuels, 2022)
The present work aims to identify alternative liquid biofuel value chain scenarios utilizing heavy metal (HM)-contaminated biomass feedstocks. The analysis is based on breaking down existing liquid biofuel value chains, focusing on the required adaptations needed for clean biofuel production. State-of-the-art and emerging liquid biofuel production options are reviewed. The potential implications caused by the HM load in the biomass feedstock are analyzed along the whole biofuel production chain, which includes pre-processing, conversion and post-processing stages. The fate of the most common HM species present in contaminated biomass is identified and graphically represented for advanced (second generation) biofuel conversion processes. This information synthesis leads to the description of alternative value chains, capable of producing HM-free biofuel. This work goes a step further than existing reviews of experiments and simulations regarding heavy metal-contaminated biomass (HMCB) valorization to biofuels since feasible value chains are described by synthesizing the findings of the several studies examined. By defining the adapted value chains, the “road is paved” toward establishing realistic process chains and determining system boundaries, which actually are essential methodological steps of various critical evaluation and optimization methodologies, such as Life Cycle Assessment, supply chain optimization and techno-economic assessment of the total value chain.